2014
DOI: 10.1371/journal.pone.0085459
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity, Impact on Carriage and Reactogenicity of 10-Valent Pneumococcal Non-Typeable Haemophilus influenzae Protein D Conjugate Vaccine in Kenyan Children Aged 1–4 Years: A Randomized Controlled Trial

Abstract: BackgroundThe impact on carriage and optimal schedule for primary vaccination of older children with 10-valent pneumococcal non-typeable Haemophilus influenzae protein-D conjugate vaccine (PHiD-CV) are unknown.Methods600 Kenyan children aged 12–59 months were vaccinated at days 0, 60 and 180 in a double-blind randomized controlled trial according to the following vaccine sequence: Group A: PHiD-CV, PHiD-CV, diphtheria/tetanus/acellular pertussis vaccine (DTaP); Group B: PHiD-CV, DTaP, PHiD-CV; Group C: hepatit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 29 publications
2
34
1
Order By: Relevance
“…The carriage rate of non-vaccine serotypes remained unchanged at 45·7% (16 of 35). These findings are consistent with the patterns observed in the parent study [21]. …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The carriage rate of non-vaccine serotypes remained unchanged at 45·7% (16 of 35). These findings are consistent with the patterns observed in the parent study [21]. …”
Section: Resultssupporting
confidence: 93%
“…Notably, these kinetics of memory B cells differed from those of plasma antibodies, suggesting independence in the generation of the two compartments. There were significant increases in plasma antibodies against all assessed serotypes after each dose of PHiD-CV, with the highest increases being observed after the first dose [21]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, randomized controlled intervention studies assessing the direct effect of different PCVs on carriage, reported an early decrease of S. pneumoniae carriage among vaccinated individuals [15,16]. Implementation of PCV7 did not affect overall S. pneumoniae carriage prevalence in our population-based study.…”
Section: Discussioncontrasting
confidence: 46%
“…Importantly, studies from South Africa, Kenya and Gambia show promising effectiveness [15,1821]. In a study on patients with IPD in Uganda between 2003–2007 the potential vaccine serotype coverage was 55% for PCV7, 58% for PCV10 and 79% for PCV13 [22].…”
Section: Introductionmentioning
confidence: 99%